Acupuncture for Mild Cognitive Impairment and Dementia: An Overview of Systematic Reviews - He, Wenbo; Li, Meixuan; Han, Xuemei; Zhang, Wei (Frontiers in Aging Neuroscience, 2021)
Background: Dementia is a gradual decline in cognitive ability and is becoming more common in our elderly population. Mild cognitive impairment (MCI) is defined as a slight clinical deterioration of memory capacity, below the level of normal aging, but does not constitute a clinical diagnosis of dementia. To date, no interventions have been proven to fully cure MCI and dementia. Purpose: To evaluate the potential effectiveness and safety of acupuncture for mild cognitive impairment (MCI) and dementia, and evaluate the methodological quality of SRs. Methods: We conducted a literature search for SRs with meta-analyses (MAs) in seven Chinese and international databases through 1 October, 2020. The basic characteristics of the included SRs/meta-analyses and the basic information of the original included randomized controlled trials (RCTs) were extracted by three reviewers independently. A meta-analysis of the original RCTs from the included SRs/meta-analyses was performed using Stata 12.0 software. The Assessing the Methodological Quality of Systematic Reviews 2 (AMSTAR-2) was used to assess the methodological quality of the included SRs/meta-analyses, and the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) was used to rate the quality of evidence. Results: A total of 35 SRs/meta-analyses were included and the majority showed that acupuncture was more effective than western medicine or conventional therapy for MCI and dementia (Odds ratio (OR) =1.39; 95% confidence interval (CI): 1.24, 1.56). There was a statistically significant difference in the Mini Mental State Examination (MMSE) score (WMD=1.23; 95% CI: 0.78, 1.68; p<0.00001), and there was no significant improvement in the activities of daily living (ADL) score (WMD =1.58; 95% CI: -0.02, 3.18; p=0.053). The assessment results of AMSTAR-2 showed that the methodological quality of most included SRs/meta-analyses was critically low; the lowest score were item 2, 7 and 10. For GRADE, of the 73 outcomes, 50 (68.5%) outcomes were low or very low quality and 23 (31.5%) outcomes were moderate quality. Conclusions: Acupuncture can be considered as an alternative for treatment of MCI and dementia when western medicine or other therapies are contraindicated. More high-quality evidence is needed to further determine the effectiveness of acupuncture.